2012
DOI: 10.1021/jf204974s
|View full text |Cite
|
Sign up to set email alerts
|

Faster Fermentation of Cooked Carrot Cell Clusters Compared to Cell Wall Fragments in Vitro by Porcine Feces

Abstract: Plant cell walls are the major structural component of fruits and vegetables, which break down to cell wall particles during ingestion (oral mastication) or food processing. The major health-promoting effect of cell walls occurs when they reach the colon and are fermented by the gut microbiota. In this study, the fermentation kinetics of carrot cell wall particle dispersions with different particle size and microstructure were investigated in vitro using porcine feces. The cumulative gas production and short-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 40 publications
1
34
1
Order By: Relevance
“…6 It appears that the plant cellular composition or architecture has a more significant impact than particle size or available surface area (exposed to the faecal microbiota). Larger banana particles may have contained a higher proportion of more fermentable cell wall structures.…”
Section: Effects Of Fruit and Particle Size On Fermentation Kineticsmentioning
confidence: 99%
See 2 more Smart Citations
“…6 It appears that the plant cellular composition or architecture has a more significant impact than particle size or available surface area (exposed to the faecal microbiota). Larger banana particles may have contained a higher proportion of more fermentable cell wall structures.…”
Section: Effects Of Fruit and Particle Size On Fermentation Kineticsmentioning
confidence: 99%
“…6), 26 followed by in vitro gastrointestinal digestion 6 and centrifugation at 3000g for 10 min (Avant®JE centrifuge, JA14 rotor). 6), 26 followed by in vitro gastrointestinal digestion 6 and centrifugation at 3000g for 10 min (Avant®JE centrifuge, JA14 rotor).…”
Section: Preparation Of Fruit Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxically, multicellular clumps of carrot cells were found to be more rapidly fermented than cell wall fragments, probably because the intercellular spaces and angles between cells in multicellular clusters provided colonization sites for colonic bacteria (Day et al 2012). There is, however, likely to be an optimal size at which increased colonization sites are counterbalanced by inaccessibility in large particles.…”
Section: A Colonic Digestionmentioning
confidence: 99%
“…These cellular structures remained visually intact during in vitro colonic fermentation with smaller particles (<1 mm) fermenting more rapidly that larger ones. In contrast, fermentation of carrot cell clusters showed that particles measuring approximately 150-300 µm were more rapidly fermented than smaller clusters or single cells [9]. These studies suggest that the intactness of cellular structures may affect fruit and vegetable functionality in the gut.…”
Section: Introductionmentioning
confidence: 80%